A Cross Sectional Study to Assess the Knowledge, Attitude and Practice towards Voluntary Blood Donation amongst Undergraduate Students of a Medical College in North India (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The youth of the country especially college students can serve as a readily available pool ofvoluntary blood donors and help tide away some of the scarcity of blood and blood products. This study wasconducted to determine the Knowledge, attitude and practice (KAP) regarding Voluntary Blood Donationamong medical undergraduate studentsand to assess the factors which can lead to a subsequent increase inthe same.Method: A cross-sectional descriptive study was conducted amongst 500 undergraduate medical studentsstudying at Government Medical College, Patiala, Punjab using a structured, self-administered questionnaireregarding KAP.Results: The mean age of the 500 participating students was 20.46 years with a standard deviation of1.5 of which 55.2% were females.71.2% and 61.4% students had correct knowledge regarding intervalbetween blood donation for males and females respectively but the knowledge regarding common causesof deferral was less. Posters and pamphlets were the most common sources of information regarding blooddonation.92.6% students had a good attitude towards blood donation. 127 (25.4%) students had donatedblood previously and 17 (3.4%) of them had donated blood more than once in a year.Conclusion: The students had a fair knowledge about VBD and the majority had a favourable attitudetowards it. Steps should be taken to increase the awareness regarding VBD since early sensitisation towardsits importance can motivate students to become voluntary blood donors, making them major contributorsto the blood donor pool throughout their adulthood and help in overcoming blood shortage in the country.
Keywords: Knowledge, Attitude, Practice (KAP), Voluntary Blood Donation (VBD), medical students